2019
DOI: 10.3389/fonc.2019.01344
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: RORα Suppresses Epithelial-to-Mesenchymal Transition and Invasion in Human Gastric Cancer Cells via the Wnt/β-Catenin Pathway

Abstract: Retinoid-related orphan receptor alpha (RORα) is involved in tumor development. However, the mechanisms underlying RORα inhibiting epithelial-to-mesenchymal transition (EMT) and invasion are poorly understood in gastric cancer (GC). This study revealed that the decreased expression of RORα is associated with GC development, progression, and prognosis. RORα suppressed cell proliferation, EMT, and invasion in GC cells through inhibition of the Wnt/β-catenin pathway. RORα overexpression resulted in the decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Scutellarin reversed hypoxia-induced EMT in breast cancer cells through the PI3K/Akt and MAPK pathways [34]. Besides, it is also reported that Wnt signaling pathway promotes tumor progression and metastasis in various cancers [41]. Previous studies have shown that the Wnt/b-catenin pathway is activated in gastric cancer [42], and contributes to tumor malignancy in gastrointestinal stromal tumor [43].…”
Section: Discussionmentioning
confidence: 96%
“…Scutellarin reversed hypoxia-induced EMT in breast cancer cells through the PI3K/Akt and MAPK pathways [34]. Besides, it is also reported that Wnt signaling pathway promotes tumor progression and metastasis in various cancers [41]. Previous studies have shown that the Wnt/b-catenin pathway is activated in gastric cancer [42], and contributes to tumor malignancy in gastrointestinal stromal tumor [43].…”
Section: Discussionmentioning
confidence: 96%
“…Also, in melanomas it is known that Axin1 regulates the level of β-catenin that has a synergy effect with a BRAF-V600E inhibitor (PLX4720) [51]. Recently, polymorphisms of the Axin1 gene were found to be associated with bladder cancer risk [52]. Axin2 has opposing functions in cancers.…”
Section: Wnt Signaling Pathway In Diverse Cancersmentioning
confidence: 99%
“…In 2012, a novel mechanism for the stabilization of p53 protein expression via activation of the orphan nuclear receptor-RORα was introduced [77]. Figure S1B, C) of [78]). It has been found that overexpression of RORα could inhibit the proliferation, EMT, and invasion of these cells [78].…”
Section: Discovery Of Synthetic Anti-cancer Compounds Sr1078 That Stamentioning
confidence: 99%
“…Figure S1B, C) of [78]). It has been found that overexpression of RORα could inhibit the proliferation, EMT, and invasion of these cells [78]. It has been pointed out that stimulation of G-protein-coupled receptors by glucagon or epinephrine activates Lats1/2 kinase activity, thereby inhibiting the YAP function [79].…”
Section: Discovery Of Synthetic Anti-cancer Compounds Sr1078 That Stamentioning
confidence: 99%